2005
DOI: 10.2220/biomedres.26.159
|View full text |Cite
|
Sign up to set email alerts
|

Histological observations on the microenvironment of osteolytic bone metastasis by breast carcinoma cell line

Abstract: Bone tissue, with its dynamic microenvironment featuring osteoclastic bone resorption, angiogenesis and matrix degradation, appears to facilitate proliferation of tumor cells after the onset of bone metastasis. In this study, we examined metastatic lesions in the femora of BALB/c nu/nu mice two weeks after intracardiac injection with human breast carcinoma MDA-231 cells. Histopathological observations showed the metastatic lesions close to the chondro-osseous junction, and revealed MDA-231 cells loosely interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
4
20
1
Order By: Relevance
“…Breast car-easily observe macrophage/monocytes, lymphocytes and osteoclasts which localize at metastatic sites. F4/80 can recognize macrophage/monocyte lineage cells, but not osteoclasts in mouse bone as reported previously (34,43). In contrast, tartrate-resistant acid phosphatase (TRAP) staining can distinguish the osteoclastic lineage from mouse macrophage/ monocytes, though not from human macrophages which can express TRAP5a.…”
supporting
confidence: 68%
“…Breast car-easily observe macrophage/monocytes, lymphocytes and osteoclasts which localize at metastatic sites. F4/80 can recognize macrophage/monocyte lineage cells, but not osteoclasts in mouse bone as reported previously (34,43). In contrast, tartrate-resistant acid phosphatase (TRAP) staining can distinguish the osteoclastic lineage from mouse macrophage/ monocytes, though not from human macrophages which can express TRAP5a.…”
supporting
confidence: 68%
“…Carcinoma-associated fibroblasts are implicated in extracellular matrix production, which provides a lattice that facilitates cancer progression; they are one of the main sources of VEGF, thus providing more nutriment to the metastastic cells (Kalluri and Zeisberg, 2006). Shimamura et al (2005) have investigated the microenvironment of osteolytic metastases caused by MDA-MB 231 breast carcinoma cells in nude mice. At 2 weeks after an intracardiac injection with MDA-MB 231 cells, foci of tumour cells were associated with osteoclastogenesis together with angiogenesis related to intense the expression of VEGF (Shimamura et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Shimamura et al (2005) have investigated the microenvironment of osteolytic metastases caused by MDA-MB 231 breast carcinoma cells in nude mice. At 2 weeks after an intracardiac injection with MDA-MB 231 cells, foci of tumour cells were associated with osteoclastogenesis together with angiogenesis related to intense the expression of VEGF (Shimamura et al, 2005). In our study, we have also found specific modifications in the bone microenvironment around the tumour foci with expression of M-CSF, Dkk-1 and RANKL in non-osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…They rapidly become resistant to chemotherapy and radiotherapy and are often very painful necessitating local and/or alternative treatments in order to reduce the osteolysis triggered by the cancerous cells. The osteolysis is due to local activation of the osteoclasts and macrophages by factors synthesized by the tumor cells (Shimamura, T., et al, 2005). It is the osteolysis that is very often responsible for the pain.…”
Section: Introductionmentioning
confidence: 99%